Investigating the response of hydrological processes to El Niño events using a 100-year dataset from the western Pacific Ocean - Natasha Sekhon; Carlos Primo C. David; Mart Cyrel M. Geronia; Manuel Justin G. Custado; Daniel E. Ibarra (Journal of Hydrology: Regional Studies, 2022)
Study region: Western Tropical Pacific Ocean (Philippines) Study focus: El Niño Southern Oscillation (ENSO) modulates rainfall amount variability and, by extension, river discharge for the Philippines on seasonal to interannual temporal scales. The El Niño phase of ENSO considerably decreases rainfall amounts on a seasonal scale with varying degrees of heterogeneity across the Philippines. The hydrological response of El Niño on an interannual scale is relatively immature. To investigate the hydrological response, a composite time series of 29 rainfall and 61 river discharge stations spanning 1901–2020 and 1908–2017 C.E., respectively, and covering the four major climate types in the Philippines were critically assessed. New hydrological insights for the region: Our statistical analyses results of a 100-year dataset demonstrate a decreasing trend compared to pre-El Niño conditions for both river discharge and rainfall. The median response suggests the decreasing trend can last up to 7 years regardless of climate type. Rainfall amount returns to pre-El Niño conditions faster than river discharge. The sign (increasing or decreasing) of the hydrological response is either decreasing, if at conception of an El Niño phase, or increasing, if at the termination of an El Niño phase. Our results have implications for water resource management and water resiliency of island nations that strongly rely on the timely delivery of rainfall amount. Further, our results highlight the legacy effects of El Niño events that likely initiate long-term droughts for island nations in western tropical Pacific Ocean.